1989
DOI: 10.1017/s0031182000058686
|View full text |Cite
|
Sign up to set email alerts
|

Origin, kinetics of circulation and fatein vivoof the major excretory–secretory product ofAcanthocheilonema viteae

Abstract: The excretions-secretions (E-S) of Acanthocheilonema viteae consist mainly of one product, molecular weight 62kDa. This molecule is synthesized during the vertebrate phase of the parasite life-cycle and is first detectable in the E-S of L4 parasites. It is cross-reactive with E-S of human filarial parasites as a consequence of possessing a phosphorylcholine (PC) moiety. The 62 kDa molecule has been employed as a model for the study of the origin and fate of filarial E-S. Immunohistological analysis has shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
63
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 29 publications
(21 reference statements)
2
63
0
Order By: Relevance
“…Titanji* Parasite, 1997, 4, 351-358 of the cuticle (Haque & Capron, 1986). Some of these ESP have been found to be biologically active molecules such as enzymes (Harnett et al, 1989) which aid in the migration of these tissue-dwelling parasites through host tissues. By virtue of their direct contact with the host immune system, they may also persistently stimulate the host immune system, causing local inflammatory responses (Maizels et al, 1982;Ottessen, 1984;Philipp étal, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Titanji* Parasite, 1997, 4, 351-358 of the cuticle (Haque & Capron, 1986). Some of these ESP have been found to be biologically active molecules such as enzymes (Harnett et al, 1989) which aid in the migration of these tissue-dwelling parasites through host tissues. By virtue of their direct contact with the host immune system, they may also persistently stimulate the host immune system, causing local inflammatory responses (Maizels et al, 1982;Ottessen, 1984;Philipp étal, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest, filarial nematodes have been shown to secrete glycoproteins containing a known immunomodulator, phosphorylcholine (PC) (2,4). We have demonstrated that the PC moiety of one such molecule, ES-62, a glycoprotein that is a major ES of the rodent filarial parasite Acanthocheilonema viteae (5) and has homologues in human filarial nematodes, inhibits Ag receptor-driven B and T cell proliferation by selectively uncoupling the Ag receptors from key downstream proliferative signaling pathways (4, 6 -10). Thus, although ES-62-mediated inhibition of lymphocyte activation is not targeted against the early Ag receptor-coupled phospholipase C (PLC-␥)-mediated hydrolysis of phosphatidylinositol 4,5-bisphosphate, it selectively down-regulates certain protein kinase C isoforms and desensitizes protein tyrosine kinase-dependent coupling of the Ag receptors to the phosphatidylinositol 3-kinase and the Ras-ErkMAP kinase signaling cascades (6 -9).…”
mentioning
confidence: 99%
“…ES-62 is a secreted PC-containing glycoprotein of the rodent filarial nematode Acanthocheilonema viteae (11). Subcutaneous injection of this parasite product into BALB/c mice results in the generation of high levels of immunoglobulin G1 (IgG1) antibody, but virtually no IgG2a, directed against the non-PC epitopes of the molecule (8).…”
mentioning
confidence: 99%
“…Groups of four 6-to 8-week-old female BALB/c mice were given a total of four subcutaneous injections of purified parasite material (3 g per injection), each 1 week apart. Serum samples were collected at day 0 and day 35 and stored at Ϫ20°C until assayed by enzyme-linked immunosorbent assay (ELISA) (11).…”
mentioning
confidence: 99%